Critical currents of Rutherford MgB2 cables compacted by two-axial rolling. (2nd November 2016) - Kopera, L; Kováč, P; Kulich, M; Melišek, T; Rindfleisch, M; Yue, J; Hušek, I
Abstract: Two types of Rutherford cables made of two strand layers of commercial MgB2 wires manufactured by Hyper Tech Research, Inc. have been made. Flat rectangular cables consisting of 12 single-core MgB2 /Nb/Cu10Ni, or 6-filaments MgB2 /Nb/Cu strands, both of diameter 390 mewm, were assembled using a back-twist cabling machine with transposition length of 20 mm. In order to analyze impact of the cable compaction on critical currents, cables were two-axially rolled, each by a single step reduction of 3.5%−29.7% to thickness range of 0.775−0.62 mm. It was found that by increasing the packing factor (PF) of cable above 0.79, the critical current begins to increase. It is improved nearly two times up to the PF limit 0.89. Compaction over the PF limit introduced cable degradation and decrease of critical current. Bending tests applied to cables showed that critical current degradation starts below the bending diameter 120 mm for 6-filaments Cu sheath and 70 mm for single-core Cu10Ni sheath cable. Tensile tests showed similar irreversible strain values for the both types of cables. Rutherford cables assembled of single-core strands are promising for low field (2.7−4 T) applications where low bending diameters are required.